Heart failure supported by veno-arterial extracorporeal membrane oxygenation (ECMO): a systematic review of pre-clinical models - Sacha Rozencwajg; Silver Heinsar; Jacky Suen; Gianluigi Li Bassi; Maximilian Malfertheiner; Leen Vercaemst; Lars Mikael Broman; Matthieu Schmidt; Alain Combes; Indrek Rätsep; John F. Fraser; Jonathan E. Millar; et al. (Intensive Care Medicine Experimental, 2020)
Abstract Objectives Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is increasingly being used to treat patients with refractory severe heart failure. Large animal models are developed to help understand physiology and build translational research projects. In order to better understand those experimental models, we conducted a systematic literature review of animal models combining heart failure and VA-ECMO. Studies selection A systematic review was performed using Medline via PubMed, EMBASE, and Web of Science, from January 1996 to January 2019. Animal models combining experimental acute heart failure and ECMO were included. Clinical studies, abstracts, and studies not employing VA-ECMO were excluded. Data extraction Following variables were extracted, relating to four key features: (1) study design, (2) animals and their peri-experimental care, (3) heart failure models and characteristics, and (4) ECMO characteristics and management. Results Nineteen models of heart failure and VA-ECMO were included in this review. All were performed in large animals, the majority (n = 13) in pigs. Acute myocardial infarction (n = 11) with left anterior descending coronary ligation (n = 9) was the commonest mean of inducing heart failure. Most models employed peripheral VA-ECMO (n = 14) with limited reporting. Conclusion Among models that combined severe heart failure and VA-ECMO, there is a large heterogeneity in both design and reporting, as well as methods employed for heart failure. There is a need for standardization of reporting and minimum dataset to ensure translational research achieve high-quality standards.